Leaders’ ambition and followers’ cheating behavior: The role of performance pressure and leader identification - Adeel, Ahmad; Kee, Daisy Mui Hung; Mubashir, Anila Sadaf; Samad, Sarminah; Daghriri, Yahya Qasim (Frontiers in Psychology, 2023)
We seek to understand why and how leaders’ actions that are positive from organizational perspectives, drive to engage employees in cheating behaviors. The proposed mediated moderation model was tested in two separate studies, study 1 and study 2, with data collected from police officers and employees of Islamic banking respectively, and then analyzed with Mplus for random coefficient models for direct effects, indirect effects, and for mediated moderation. It was found that leaders’ ambitions may enhance performance pressure on the subordinates, which in turn promotes their cheating behavior. Overall, we found that the traditional view of ambition theory only emphasizes good mechanisms such as motivation. However, to integrate with a social identity perspective, ambition would also cause pressure and pressure rather than motivation. Additionally, leaders' ambitions are more strongly and positively related to the performance pressure and cheating behaviors of employees when subordinates also have high leader identification. The findings of this research suggested that leaders’ positive workplace behavior could also spawn subordinates' unethical behaviors. Through this research, we can help policymakers understand that leaders’ positive desire in general and ambition, in particular, may not be necessarily associated with subordinates' positive behaviors. Our results revealed that internalized with performance pressure, the leaders' ambition is associated with subordinates' cheating behavior. The findings of this research will help policymakers understand what might be promoting unethical behavior of employees. The cheating behavior of employees is not a singular level phenomenon of subordinates, it could also be triggered by contextual factors. Therefore, in developing policies for reducing the chance of cheating at work, the policymakers should also focus on the contextual factors that might be promoting cheating.